Impact of cigarette smoke on physical‐chemical and molecular proprieties of human skin in an ex vivo model. Issue 11 (9th November 2020) - Percoco, Giuseppe; Patatian, Angela; Eudier, Florine; Grisel, Michel; Bader, Thomas; Lati, Elian; Savary, Géraldine; Picard, Céline; Benech, Philippe
Abstract: Background: This is a study about the skin ageing exposome, focusing on the effect of cigarette smoke. Human living skin explants (HSE) were exposed to cigarette smoke (CS) of two cigarettes for 2 hours using a custom‐made exposure chamber, the Pollubox ® . Effects on the surface physico‐chemistry and molecular properties of the skin were analyzed and reported for the first time. Basic Procedures: To this end, transcriptomic study followed by immunohistochemistry, MDA (Malondialdehyde Dosage), and surface physio‐chemistry data: surface free energy determination, TEWL (Trans Epidermal Water Loss), skin pH and FT‐IR (Fourier Transform‐Infrared) spectroscopy of the explant were collected from untreated and treated HSE. Main Findings: Results showed a decrease of the total surface free energy of the treated HSE. This decrease reflected higher interactions with polar compounds from the environment and consequently a decrease of the surface hydrophobicity. Additionally, an increase of TEWL and skin pH was observed after treatment. The transcriptomic analysis showed downregulation of mitochondrial genes (PON2‐NDUFA4L2‐ATP1A1‐ALDH2‐PRODH) combined with an increase of MDA in CS‐treated HSE. Conclusions: CS‐induced oxidation of lipids at HSE surface alters the skin barrier: interactions with polar products are enhanced and the lipid chain packing at the surface is modified. Consequently, skin permeability could increase which correlated with repression of CA9 and AQP1 genes. Beside activation of AHR‐NRF2 pathway in CS‐exposed HSE, our results suggested that mitochondrial functions were strongly impacted and oxidized lipids failed to be eliminated promoting skin barrier alteration. A mitophagy activity was suggested through the confirmation of PINK1 accumulation in the epidermis by immunostaining.